Turbulent flow heat transfer and fluid friction in helical graterlike turbulator inserted tubes - Tanyildizi, Vedat; Ayhan, Teoman; Karabay, Hasan; Eren, Haydar (Publ by ASME, 1992)
The subject of enhanced heat transfer has been developing during the past twenty-five years, especially for heat-exchanger applications. Efforts are being made to develop better heat transfer surfaces to obtain compact and less expensive but more efficient heat exchange equipments by the reason of great emphasis on economic savings considerations. Many techniques have been applied or studied with several degrees of success. 'Helical Graterlike turbulators' filted in the tubes of bare inside surfaces were tested in this work for the first time and gave a considerable increase in heat transfer rate without very much increase in friction power in turbulent flow over the range 5,000 < Re < 20,000. Nusselt numbers are 2 - 3 times higher those for the tube of bare inside surface for the Reynolds number of 10,000. Graterlike turbulators with helical vane arrangement were expected to produce some helical flow in the neighbourhood of the turbulator body, superimposed upon the main axial flow and influence the velocity distribution, the turbulence level and turbulent shear stress. Decrease on heat transfer with increasing helix angles show that helical arranged vanes do not help swirling as much as thought and also give less turbulence than vanes with no helix angle do. To reduce the friction power needs further works. This is the preliminary work to optimise their dimensions and to study their frictional and heat transfer performance. To develop suitable momentum and heat transfer correlations is also aimed.
Proceedings of the 1992 Engineering Systems Design and Analysis Conference -- 29 June 1992 through 3 July 1992 -- Istanbul, Turk -- 16917
Keywords: Flow of Fluids - Friction; Heat Exchangers - Design; Heat Transfer - Mathematical Models; Helical Graterlike Turbulators; Helix Angle; Flow of Fluids